Physical activity and self-esteem: testing direct and indirect relationships associated with psychological and physical mechanisms - Zamani Sani SH; Fathirezaie Z; Brand S; Pühse U; Holsboer-Trachsler E; Gerber M; Talepasand S (Neuropsychiatric Disease and Treatment)
Seyed Hojjat Zamani Sani,1 Zahra Fathirezaie,1 Serge Brand,2 Uwe Pühse,3 Edith Holsboer-Trachsler,2 Markus Gerber,3 Siavash Talepasand4 1Department of Motor Behavior, Faculty of Physical Education and Sport Science, University of Tabriz, Tabriz, Iran; 2Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders (ZASS), 3Department of Sport, Exercise and Health, Sport Science Section, University of Basel, Basel, Switzerland; 4Department of Psychology and Educational Sciences, Semnan University, Semnan, Iran Abstract: In the present study, we investigated the relationship between physical activity (PA) and self-esteem (SE), while introducing body mass index (BMI), perceived physical fitness (PPF), and body image (BI) in adults (N =264, M =38.10 years). The findings indicated that PA was directly and indirectly associated with SE. BMI predicted SE neither directly nor indirectly, but was directly associated with PPF and both directly and indirectly with BI. Furthermore, PPF was directly related to BI and SE, and a direct association was found between BI and SE. The pattern of results suggests that among a sample of adults, PA is directly and indirectly associated with SE, PPF, and BI, but not with BMI. PA, PPF, and BI appear to play an important role in SE. Accordingly, regular PA should be promoted, in particular, among adults reporting lower SE. Keywords: physical activity, self-esteem, physical fitness, body image, adults